Bioinspired Bilayer Structural Color Hydrogel Actuator with Multienvironment Responsiveness and Survivability. Issue 12 (16th August 2019) - Zhang, Zhuohao; Chen, Zhuoyue; Wang, Yu; Chi, Junjie; Wang, Yuetong; Zhao, Yuanjin
Abstract: Inspired by the actuator mechanism of Venus flytrap leaves, presented is a bilayer structural color hydrogel actuator by employing a hybrid inverse opal scaffold to join the poly(acrylic acid‐ co ‐acrylamide) layer and the poly( N ‐isopropylacrylamide) layer together. The nanostructure of the inverse opal scaffold imparts the bilayer hydrogel with brilliant structural color, which can show a reversible coloration switch during the structural change. An internal water distribution occurs in the composite bilayer hydrogel during the heating or cooling process because of the opposite thermo‐responsiveness of the two hydrogels. Thus, this intelligent soft material can work in various environments and break the limitation of aqueous media of most structural color hydrogels. In addition, the water transference of the bilayer hydrogel enables the material with bending/unbending deformations and hence a series of complex motions like screwing, catching, and releasing can be achieved. Attractively, with the integrating of graphene oxide, the hydrogel systems can even be imparted with near‐infrared remote responsiveness to both of their color change and 3D deformation. These features of the bioinspired bilayer structural color hydrogel indicate its potential values in a variety of intelligent soft material applications. Abstract : A novel bilayer structural color hydrogel actuator is designed and fabricated, which can function in multiple working environments by using a hybrid inverse opal scaffold to join the poly(acrylic acid‐ co ‐acrylamide) layer and the poly( N ‐isopropylacrylamide) layer together. It is expected to open a new chapter in the designing and the fabrication of coloration sensing, intelligent soft actuators, manipulators, etc.